Association between comorbidities and blood pressure trajectories in patients with hypertension. (25th November 2020) - Canoy, D; Tran, J; Norton, R; Ayala Solares, R; Conrad, N; Nazarzadeh, M; Raimondi, F; Salimi-Khorshidi, G; Rodgers, A; Rahimi, K
Abstract: Background: Our knowledge of how to better manage elevated blood pressure in presence of comorbidities is limited; in part due to exclusion or underrepresentation of multimorbid patients from major clinical trials. Purpose: To investigate the burden and types of comorbidities in patients with hypertension, to assess how such comorbidities and other variables affect blood pressure levels over time. Methods: The study was conducted using linked electronic health records from the UK Clinical Practice Research Datalink study from its inception on 1 January 1985 to 30 September 2015. Using linked electronic health records, we compared systolic blood pressure levels among 295, 487 patients with diagnosed hypertension by type and numbers of major comorbidities from at least 5 years before to up to 10 years after hypertension diagnosis. We used a multiple landmark cohort design in order to investigate associations prospectively with time-updated information that takes advantage of the dynamic nature of electronic health records. Results: Time-updated multivariable linear regression analyses showed that the presence of more comorbidities was independently associated with lower blood pressure during follow-up. This negative association was not specific to particular types of comorbidities; although associations were stronger in those with pre-existing cardiovascular disease. Tracking patients backwards to years prior to hypertension diagnosis revealed that the association between comorbidities and blood pressure were even more pronounced in years before hypertension diagnosis. Despite substantial declines in blood pressure in the first year after diagnosis, subsequent changes were modest, with no evidence of a more rapid decline in those with more or specific types of comorbidities. Conclusions: Blood pressure levels at which patients were diagnosed with hypertension varied substantially and were lower when patients had more comorbidities. This early selection bias was a key determinant of long-term differences in blood pressure by comorbidity status and provides an additional explanation for the lower blood pressure in multimorbid patients. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): National Institute for Health Research Oxford Biomedical Research Centre, Rhodes Trust and Clarendon Fund